Effect of Aeolian Sand Powder Addition on Frost Resistance of Concrete Pavement - Ou Zhao; Xuefeng Deng (International Journal of Analytical Chemistry)
In order to solve the problem of exploring the freeze-thaw characteristics of modified aeolian sand mixed with cement and silt, the authors propose a freeze-thaw cycle test of modified aeolian sand under the condition of mixing 5% cement and silt with different contents. In this experiment, under freeze-thaw conditions, its intensity decay and mass volume change law and the changes of freeze-thaw characteristics were comprehensively characterized by multiple indicators. The result shows that, after two freeze-thaw cycles, the compressive strength and peak strain of the improved aeolian sand were positively correlated with the silt content. With the increase of the number of freeze-thaw cycles, the compressive and antidestruction capacity of the improved aeolian sand with high silt content and low silt content decreased significantly. 15% silt content improves the structural stability of aeolian sand. It is proved that the authors’ experiment can intuitively and effectively reflect the change law of soil strength after freezing and thawing of such improved aeolian sandy soil, which has displayed significance.